1985
DOI: 10.1021/ic00203a016
|View full text |Cite
|
Sign up to set email alerts
|

Role of the H3O2 bridging ligand in coordination chemistry. 1. Structure of hydroxoaquametal ions

Abstract: and activation energies (0.03 eV), although the interplanar spacing for the Ge material is ~0.3 Á shorter than that of the Ga analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
10
0
Order By: Relevance
“…Ϫ are well documented for doubly bridged hydroxo dimers of metals (see Springborg, 1988;Ardon and Bino, 1985) where they dramatically affect the stability of the dimer and the Brønsted acid-base properties. It seems likely that similar bridges will be observed on mineral surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ are well documented for doubly bridged hydroxo dimers of metals (see Springborg, 1988;Ardon and Bino, 1985) where they dramatically affect the stability of the dimer and the Brønsted acid-base properties. It seems likely that similar bridges will be observed on mineral surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This synthon involves H bonds classified by Desiraju as strong bonds [ 57 ]. H 3 O 2 − anions can be seen as bridging ligands in which the O-O bond length is very short and varies between 2.44 and 2.56 A [ 58 , 59 , 60 , 61 ]. The H 3 O 2 − ligand is formed from one water ligand that may hydrolyze to a hydroxo ligand, leading to a strong H bond between the hydroxo ligand of one ion and an aquo ligand of another ion [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…H 3 O 2 − anions can be seen as bridging ligands in which the O-O bond length is very short and varies between 2.44 and 2.56 A [ 58 , 59 , 60 , 61 ]. The H 3 O 2 − ligand is formed from one water ligand that may hydrolyze to a hydroxo ligand, leading to a strong H bond between the hydroxo ligand of one ion and an aquo ligand of another ion [ 60 , 61 ]. The first example of a µ-H 3 O 2 − bridging ligand in a MOF material has been reported by Monge et al [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising because H 3 O 2 – anions are quite stable in the gas phase2 and can even be crystallised as isolated H 3 O 2 – anions in the solid state 3. In the meantime, small inorganic complexes containing such H 3 O 2 linkages have been reported for most of the first‐row transition‐metal ions (V,4 Cr,5,6 Fe,7 Co,6,8 Ni,9,10 Cu10 and Zn11), as well as for Mo,12 W12 and Ru 13. In several cases, F. Meyer et al have shown that it is possible to selectively obtain the μ‐OH or the M–H 3 O 2 –M form by fine‐tuning the ligand environment 9b,14.…”
Section: Introductionmentioning
confidence: 99%